Character Identity Contruction through Linguistic Variation in Sherlock Holmes: A Third Wave Sociolinguistic Reading - Tiara Julia Putri (Jurnal Dieksis ID, 2026)
This study is urgent because it reveals how linguistic variation in Sherlock Holmes constructs and represents character identity through a Third Wave sociolinguistic perspective, thereby enriching our understanding of the relationship between language, identity, and social meaning in literary works. This study explores how Sherlock Holmes’ character identity is intricately formed through linguistic variation, using the Third Wave sociolinguistic framework as the primary analytical tool. This research bridges classical literary studies with modern sociolinguistic perspectives, which view identity as a performative and strategic social practice rather than a fixed psychological trait. The objective of this research is to examine how identity is constructed and performed as a strategic social practice by integrating classical literary analysis with contemporary sociolinguistic perspectives, rather than treating identity as a fixed psychological attribute. Employing a descriptive qualitative method, this study analyzes 45 selected excerpts from Sir Arthur Conan Doyle’s “The Adventures of Sherlock Holmes,” with specific attention to technical registers, formal stance, and stylistic variation. The findings reveal a consistent pattern of “stylistic practice” where Holmes utilizes specific scientific terminology, such as chemistry and forensics, to demonstrate intellectual prowess and epistemic authority over his interlocutors. Furthermore, this analysis highlights Holmes’ capacity for “style-shifting,” where he adeptly alternates between high-formal Victorian registers and colloquial language to navigate and manipulate the rigid 19th-century social structures. Unlike previous studies analyzing social class through First Wave reflections, this research demonstrates that Holmes is a dynamic project, actively “constructed” through language to manage social distance and control interactional space. These findings reinforce the argument that linguistic variation is essential in creating social meaning within fictional narratives, offering significant interdisciplinary implications for English literature and sociolinguistics. This study serves as a profound theoretical resource for understanding how professional identities are indexed and maintained linguistically across various media and historical contexts, while affirming the relevance of Third Wave theory in literary studies.